2023
DOI: 10.1139/cjss-2022-0031
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the maximum peat thickness of cultivated organic soils in the southwest plain of Montreal

Abstract: Large organic deposits in the southwestern plain of Montreal have been converted to agricultural land for vegetable production. In addition to the variable depth of the organic deposits, these soils commonly have an impermeable coprogenous layer between the peat and the underlying mineral substratum. Estimations of the depth and thickness of these materials is critical for soil management. Therefore, five drained and cultivated peatlands were studied to estimate their maximum peat thickness (MPT) — a potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This study uses various land surface characterizing indices, which are basically obtained from laser scanning data, such as DEM, slope, WAM, DTW and SAGA TWI, and various cartographic materials such as a historical soil map, quaternary sediment map, etc., as well as geographical characteristics such as X and Y coordinates, continentality, and distance to rivers/lakes. Deragon et al [42] showed that in cultivated agricultural lands, the concentration of various chemical elements on the surface of the soil (thorium, uranium), various topographic indices, such as multiresolution index of the ridge top flatness and valley bottom flatness, and mid-slope position, as well as distance from each peatland's center and other covariates, can all be important in mapping organic soils using machine learning [12]. Gatis et al demonstrated that passive airborne gamma-ray spectrometric data can also be used in peat layer thickness mapping.…”
Section: Discussionmentioning
confidence: 99%
“…This study uses various land surface characterizing indices, which are basically obtained from laser scanning data, such as DEM, slope, WAM, DTW and SAGA TWI, and various cartographic materials such as a historical soil map, quaternary sediment map, etc., as well as geographical characteristics such as X and Y coordinates, continentality, and distance to rivers/lakes. Deragon et al [42] showed that in cultivated agricultural lands, the concentration of various chemical elements on the surface of the soil (thorium, uranium), various topographic indices, such as multiresolution index of the ridge top flatness and valley bottom flatness, and mid-slope position, as well as distance from each peatland's center and other covariates, can all be important in mapping organic soils using machine learning [12]. Gatis et al demonstrated that passive airborne gamma-ray spectrometric data can also be used in peat layer thickness mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Peat thickness less than 60 cm shows signs of soil degradation [38]. Soil thickness and quality may vary widely [39].…”
Section: The Need To Document More Yield-limiting Factorsmentioning
confidence: 99%
“…In this collection, manuscripts apply various machine learning techniques to address classification (Heung et al 2022;Kiss et al 2023;Saurette 2022;Sorenson et al 2022Sorenson et al , 2023 and regression (Deragon et al 2022;Paul et al 2023;Saurette 2022;Zhang et al 2022) applications in DSM. When addressing classification applications of DSM, the methods of analysis fall within two broad categories: polygon disaggregation and point-based mapping approaches.…”
Section: Advances In Soil Surveymentioning
confidence: 99%
“…In British Columbia, explore the concept of ensemble modelling in DSM research. Deragon et al (2022) characterize the spatial variability of organic deposits in the southwestern plains of Montreal by predicting three soil depth-related properties that are yet to be explored in DSM research: depth to mineral layer, coprogenous layer thickness, and maximum peat thickness. Similarly, Paul et al (2023) apply a similar approach and map the spatiotemporal dynamics of a soil property that is yet to be mapped using DSM techniques: active organic carbon.…”
Section: Advances In Soil Surveymentioning
confidence: 99%